From public schools to higher education: Exploring the motivational factors behind career transitions of EFL teachers - Alzahrani, Mohammed Abdullah (Journal of International Students, 2025)
This study explores the key factors influencing EFL teachers' transition to higher education, focusing on financial incentives, job security, professional development, and the reputation of academia. As a qualitative research study, data were collected through semistructured interviews with 18 EFL teachers who had moved from school teaching to university positions. The findings showed that higher salaries, professional development grants, pension plans, and financial stability were the main motivators for the transition. However, the transition posed significant challenges, including increased administrative responsibilities, navigating academic hierarchies, and adapting to a new academic culture. Many experienced anxieties about building their academic identity due to research expectations and pressure to publish. Despite these challenges, post-transition experiences were largely positive. The participants reported greater professional autonomy, expanded development opportunities, and increased engagement with student diversity. The findings contribute to understanding teacher career mobility, highlighting both the benefits and barriers of transitioning to university